2014
DOI: 10.1016/s2214-109x(14)70231-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of a rapid point-of-care test for active yaws: a comparative study

Abstract: Chembio Diagnostic Systems, Newcrest Mining, and the Papua New Guinea National Department of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 16 publications
1
38
1
Order By: Relevance
“…In this study, we found that in a community surveillance setting, the sensitivity and specificity of the DPP rapid diagnostic test were markedly lower than in the only previous evaluation of the assay for use in clinically active yaws [15]. There was a strong association between the sensitivity of both the T2 line (against gold standard RPR) and RPR titre and also between the T1 line (against gold standard TPPA) and RPR titre.…”
Section: Discussionmentioning
confidence: 51%
“…In this study, we found that in a community surveillance setting, the sensitivity and specificity of the DPP rapid diagnostic test were markedly lower than in the only previous evaluation of the assay for use in clinically active yaws [15]. There was a strong association between the sensitivity of both the T2 line (against gold standard RPR) and RPR titre and also between the T1 line (against gold standard TPPA) and RPR titre.…”
Section: Discussionmentioning
confidence: 51%
“…Until now, no macrolide treatment failures in the treatment of yaws have been reported. [19][20][21] A wide spectrum of macrolide-resistance mutations in 23S rRNA gene have been reported in other bacteria. However, only the A2058G and A2059G mutations (the position numbers correspond to positions on the Escherichia coli 23S rRNA gene) have been identified in TPA from clinical samples.…”
Section: Macrolide Failures In Syphilis Treatment and Frequency Of Mumentioning
confidence: 99%
“…The sensitivity of the ChemBio DPP syphilis screen was correlated to higher RPR titers, having a sensitivity of 92.0% for an RPR titer of >1:16. This study showed a lower sensitivity and specificity compared to the only prior evaluation of this assay [27], suggesting that the test is most useful for confirmation in patients with highly active clinical disease [26]. This rapid screening test does not perform as well in patients with latent disease nor useful in areas with low prevalence [26].…”
Section: Diagnosismentioning
confidence: 65%